A Review on UPQC for Power Quality Improvement in Distribution System (Global Journals of Research in Engineering, 2013)
In recent years Power engineers are increasingly concerned over the quality of the electrical power In modern power system consists of wide range of electrical electronic and power electronic equipment in commercial and industrial applications Since most of the electronic equipments are nonlinear in nature these will induce harmonics in the system which affect the sensitive loads to be fed from the system One among the many compensating devices is Unified Power Quality Conditioner UPQC which specifically aims at the integration of series-active and shunt-active power filters to mitigate any type of voltage and current fluctuations and power factor correction in a power distribution network such that improved power quality can be made available at the point of common coupling In This paper presents a comprehensive review on the unified power quality conditioner UPQC to enhance the electric power quality at distribution levels This is intended to present a broad overview on the different possible UPQC system configurations
Keywords: power quality (pq); harmonics; voltage sag; voltage swell; active power filter (apf); unified power quality conditioner (upqc)